Global data set of urban/rural agglomeration units - Giuseppe Amatulli; Thomas Ryan; P Power Ryan (PANGAEA, 2023)
Urban studies often rely on urban boundaries that have been defined by administrative units or by land use or land cover classification of satellite images. The final results of those boundaries is the categorization of urban/non-urban units in the form of a binary layer used to extract additional information (e.g., zonal statistic) from other geographical layers (e.g., land surface temperature or population density). Given the heterogeneous and continuous nature of the built-up area, binary representations contain a mixture of urban/non-urban areas that influence the results of following analyses. Here we present a way to move beyond the limitations of the binary urban/non-urban representations with a hierarchical watershed-based thresholding and segmentation approach that partitions the built-up area into more homogeneous units. The proposed algorithm, applied to the Global Human Settlement Layer, enables researchers and planners to define urban computational units in three ways - bin-unit, watershed-unit, and agglomeration-unit - depending on need and scale of analyses. We provide suggested terminology and notation style for this cross-over application of a specialized watershed algorithm. Among other possible applications, the resulting segmented, binned and agglomeration units offer alternatives to existing patch analysis methods for drawing relationships between patterns of urban development and ecological or environmental attributes.